Lipoprotein Lipase Is a Feature of Alternatively-Activated Microglia and May Facilitate Lipid Uptake in the CNS During Demyelination - Bruce, Kimberley D.; Gorkhali, Sachi; Given, Katherine; Coates, Alison M.; Boyle, Kristen E.; Macklin, Wendy B.; Eckel, Robert H. (Frontiers in Molecular Neuroscience, 2018)
Severe demyelinating disorders of the central nervous system (CNS) such as multiple sclerosis (MS), can be devastating for many young lives. To date, the factors resulting in poor remyelination and repair are not well understood, and reparative therapies that benefit MS patients have yet to be developed. We have previously shown that the activity and abundance of Lipoprotein Lipase (LPL)—the rate-limiting enzyme in the hydrolysis of triglyceride-rich lipoproteins—is increased in Schwann cells and macrophages following nerve crush injury in the peripheral nervous system (PNS), suggesting that LPL may help scavenge myelin-derived lipids. We hypothesized that LPL may play a similar role in the CNS. To test this, mice were immunized with MOG35–55 peptide to induce experimental allergic encephalomyelitis (EAE). LPL activity was increased (p<0.05) in the brain at 30 days post-injection, coinciding with partial remission of clinical symptoms. Furthermore, LPL abundance and activity was up-regulated (p<0.05) at the transition between de- and re-myelination in lysolecithin-treated ex vivo cerebellar slices. Since microglia are the key immune effector cells of the CNS we determined the role of LPL in microglia. Lipid uptake was decreased (p<0.001) in LPL-deficient BV-2 microglial cells compared to WT. In addition, LPL-deficient cells showed dramatically reduced expression of anti-inflammatory markers, YM1 (-22 fold, p<0.001), and Arg1 (-265 fold, p<0.001) and increased expression of pro-inflammatory markers, such as iNOS compared to WT cells (+53 fold, p<0.001). This suggests that LPL is a feature of reparative microglia, further supported by the metabolic and inflammatory profile of LPL-deficient microglia. Taken together, our data strongly suggest that LPL expression is a novel feature of a microglial phenotype that supports remyelination and repair through the clearance of lipid debris. This mechanism may be exploited to develop future reparative therapies for MS and primary neurodegenerative disorders (Alzheimer’s disease and Parkinson’s disease).